2022
DOI: 10.1136/lupus-2022-000778
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cardiorespiratory function and fatigue following 12 weeks of exercise training in women with systemic lupus erythematosus: a pilot study

Abstract: ObjectiveIn patients with systemic lupus erythematosus (SLE), fatigue is a debilitating symptom with poorly understood pathophysiology. Cardiorespiratory dysfunction has been hypothesised as a contributor to SLE-fatigue. The purpose of this exploratory study was to examine changes in cardiorespiratory function, following an exercise training programme in women with SLE, together with patient reported outcomes and other pathophysiological measures that may underlie SLE-fatigue.MethodsSixteen women with SLE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Therefore, no sample size was calculated for this co-primary outcome. However, since initiation of this study a pre-post study of physical activity in SLE patients reported an improvement from 4.6 (+/-1.2) to 3.1 (+/-1.4) 34 , using these estimates in a post-hoc power calculation would give us a statistical power of 95.3% with 40 completers and power of 80.5% with 24 completers.…”
Section: Sample Size Calculationmentioning
confidence: 97%
“…Therefore, no sample size was calculated for this co-primary outcome. However, since initiation of this study a pre-post study of physical activity in SLE patients reported an improvement from 4.6 (+/-1.2) to 3.1 (+/-1.4) 34 , using these estimates in a post-hoc power calculation would give us a statistical power of 95.3% with 40 completers and power of 80.5% with 24 completers.…”
Section: Sample Size Calculationmentioning
confidence: 97%